The role of plasma-molecule interactions on power and particle balance during detachment on the TCV tokamak. (8th September 2021) - Verhaegh, K.; Lipschultz, B.; Harrison, J.R.; Duval, B.P.; Fil, A.; Wensing, M.; Bowman, C.; Gahle, D.S.; Kukushkin, A.; Moulton, D.; Perek, A.; Pshenov, A.; et al.
Abstract: This paper shows experimental results from the TCV tokamak that indicate plasma-molecule interactions involving D 2 + and possibly D − play an important role as sinks of energy (through hydrogenic radiation as well as dissociation) and particles (ions) during divertor detachment if low target temperatures (<3 eV) are achieved. Both molecular activated recombination (MAR) and ion source reduction due to a power limitation effect are shown to be important in reducing the ion target flux during a density ramp. In contrast, the electron–ion recombination (EIR) ion sink is too small to play an important role in reducing the ion target flux. MAR or EIR do not occur during N2 seeding induced detachment as the target temperatures are not sufficiently low. The impact of D 2 + is shown to be underestimated in present (vibrationally unresolved) SOLPS-ITER simulations, which could result from an underestimated D 2 + D + → D 2 + + D rate. The converged SOLPS-ITER simulations are post-processed with alternative reaction rates, resulting in considerable contributions of D 2 + to particle and power losses as well as dissociation below the D2 dissociation area. Those findings are in quantitative agreement with the experimental results.